2012
DOI: 10.1260/2040-2295.3.3.373
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Aviation to Improve Safety in the Operating Room ‐ a Systematic Literature Review

Abstract: Lessons learned from other high-risk industries could improve patient safety in the operating room (OR). This review describes similarities and differences between high-risk industries and describes current methods and solutions within a system approach to reduce errors in the OR. PubMed and Scopus databases were systematically searched for relevant articles written in the English language published between 2000 and 2011. In total, 25 articles were included, all within the medical domain focusing on the compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…For decades, thought leaders in healthcare improvement have suggested that U.S. hospitals would benefit from implementing improvement initiatives supported by process reengineering principles, with leadership committed to a culture of safety and teamwork [11][12][13][14][15][16][17][18][19]. Studies of high reliability organizations and organizations with mature quality and safety programs have confirmed such approaches and further emphasized the importance of developing and empowering frontline employees to detect and eliminate process failures [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…For decades, thought leaders in healthcare improvement have suggested that U.S. hospitals would benefit from implementing improvement initiatives supported by process reengineering principles, with leadership committed to a culture of safety and teamwork [11][12][13][14][15][16][17][18][19]. Studies of high reliability organizations and organizations with mature quality and safety programs have confirmed such approaches and further emphasized the importance of developing and empowering frontline employees to detect and eliminate process failures [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic literature review offers a methodology that can be used by an interdisciplinary research team to design a transparent approach to selecting, analyzing, and synthesizing study to address its research question (Borrego, Foster, & Froyd, 2015). For instance, Wauben, Lange, and Goossens's (2012) research analyzed the similarities and differences of safety between the aviation industry and operation rooms in the hospital. Systematic literature review in other disciplines.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“… "Learning from Aviation to Improve Safety in the Operating Rooma Systematic Literature Review," described the similarities and differences between aviation and medicine industries and discussed methods and solutions with a systematic approach to reduce errors in operating rooms (Wauben, Lange, & Goossens, 2012).  Huster, Müller, Prohn, Nowak, & Herbig (2014) researched the medical risks faced by older pilots, and investigated whether the pilot risk of incapacitation for medical reasons increases with age.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…In recent years, team briefings have been proposed as potential mechanisms for standardizing team communication and functioning in the operating room. In aviation, briefings and safety checklists have long shown benefits to individuals and teams for establishing shared cognition and facilitating effective communication (Wauben et al, 2012;Russ et al, 2013). In healthcare, briefings in the operating room have been shown to reduce breakdowns in team communication (Lingard et al, 2005, Lingard et al, 2008Henrickson, et al, 2007, Papaspyros et al, 2010, improve perception of team performance (Makary et al, 2007;Papaspyros et al, 2010) and reduce the occurrence of nonroutine events (Henrickson et al, 2009;Einav et al,.…”
Section: Introductionmentioning
confidence: 99%